Technological Innovation, Design and Inclusiveness for the Manufacturing Landscapes - Viola, Serena (European Journal of Sustainable Development, 2017)
During the 20th century, several uncontrolled processes compromise the dynamics and trends of technological transitions that for centuries, had been characterizing the built environment and the manufacturing processes. In the agenda drawn by the Sustainable Transition Network, referring to manufacturing landscapes, the transition is a long process, deeply rooted to cultural and settlement specificities, to the skills of the workforce, to the opening of new markets, to the community needs. In a circular perspective for development, returning congruence to productive cycles, by linking them to the settlements vocations and communities’ skills, is the design commitment. Taking into account the systemic vision for the built and performance approach, a design strategy is experienced during three years, for the Vesuvius foodscape. It consists of three main phases: *outlining the relationships between places and manufacturing, in terms of processes, products and wastes, *mapping the technological transition processes occurring at the architectural and urban scales, *defining compatibility ranges for shortening the loops and promoting inclusive technological innovations. The project outlines a regeneration strategy informed to the following visions: 1. The productive landscape is a common good, a complex system resulting from the encounter between resources and technological thinking. 2. Strengthening the community skills is an indispensable condition for promoting regeneration. 3. The third sector, social, economic and cultural reality of a private nature but tended to produce public or collective goods and services can be a privileged actor of sustainability. Keywords: Manufactures, landscape, design, innovation, technology, reuse, reduce